Upaya Meningkatkan Kemampuan Membaca Pemahaman Menggunakan Metode Cooperative Integrated Reading and Composition pada Siswa Kelas III Sekolah Dasar - Icha Nafisa; Ibnu Muthi (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to examine the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) method in improving the reading comprehension skills of grade III elementary school students. The background of this study is the low reading comprehension skills of students who are still dominated by conventional learning methods. This study uses a library research approach with a qualitative descriptive method. Data were obtained from various scientific literature such as journals, books, research reports, and other scientific works relevant to the topic. The analysis was carried out using content analysis techniques to identify the main findings related to the application of the CIRC method. The results of the study show that the CIRC method can significantly improve students' reading comprehension skills. This method emphasizes group work, active discussion, summary preparation, and writing skills, which in an integrated manner encourage students' active involvement and strengthen their understanding of the contents of the reading. In addition to improving reading comprehension, this method also develops students' critical thinking skills, social skills, and self-confidence. However, in its implementation, challenges such as time management, group dynamics, and teacher readiness are important factors that need to be considered. In conclusion, the CIRC method is an effective and applicable learning strategy to improve reading comprehension skills in elementary schools, with the note that the implementation must be carefully designed and supported by a conducive learning environment.